Alberto Flores Galindo and his interpretation of Peruvian Independence - Peralta Ruiz, Víctor (2020)
This paper focuses on the study of the three interpretative paths that historian Alberto Flores Galindo developed in his analysis of Peruvian independence. It is argued that the double sensibility, academic and political, of this historian surfaced in his approach to issues such as the revolution of Tupac Amaru II, the Creole complicity in sustaining a counterrevolution of independence marked by social discrimination and the destruction of the project of an aristocratic and popular Andean utopia. Throughout this analysis, it is shown that the methodological trajectory of this historian was marked by the academic debates raised by the commemoration of the sesquicentennial of independence but also by the acute crisis experienced by the country in its process of democratic transition that led him to design and defend a leftist revolutionary option. Finally, it will be discussed to what extent the current historiographical knowledge on the emancipatory conjuncture reviews his interpretative essays.